The Implementation of Inclusive Education in School Providing Inclusive Education - Dewi, Wiwi Purnama; Sudadio; Fadlullah (Formosa Journal of Multidisciplinary Research, 2024)
The method used in this research is a literature study, which is a method of collecting data by understanding and studying theories from various literatures related to this research, this research aims to Inclusive Education at the Inclusive Education Provider School, Currently the implementation of inclusive education has become a necessity for students who need special guidance in regular schools. For the good of the development and social needs of students with special needs, the government provides regular schools that accept students with special needs to learn together with regular students in general classes in the same school, these schools are called Inclusive Education Provider Schools (SPPI). SPPI must be well prepared starting from the PPDB technical guidelines, curriculum, facilities and infrastructure, financing, learning methods, Special Guidance Teachers (GPK) to guide students with special needs in learning activities at schools that are tailored to the conditions of students with special needs. Students with special needs in addition to learning in regular classes also learn with a special curriculum called the Individual Learning Program (PPI).